Effect of Comprehensive Nursing Based on Cognitive Behavior on Psychological Function of Glioma Patients - Zhao YH (Dove Medical Press, 2021)
Yu-Hong Zhao, Yan Xu Operating Room, Linyi Central Hospital, Linyi, Shangdong, 276400, People’s Republic of ChinaCorrespondence: Yan XuOperating Room, Linyi Central Hospital, No. 17 Health Road, Yicheng Street, Yishui County, Linyi, Shangdong, 276400, People’s Republic of ChinaTel +86-15964811679Email 623535870@qq.comObjective: The aim of our current study is to explore the effect of comprehensive nursing based on cognitive behavior on the psychological function of glioma patients.Methods: A total of 108 patients with glioma were randomly divided into intervention group (n = 54) and control group (n = 54). Patients in the control group were given routine nursing for 3 months, while patients in the intervention group were given comprehensive nursing based on cognitive behavior for 3 months on the basis of control group. Parameters such as scores of simplified Fear of Progression Questionnaire-Short Form (FoP-Q-SF), Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) as well as cancer-related fatigue and quality of life (QOL) were compared before and after the intervention.Results: No significant difference was observed in the scores of FoP-Q-SF, SAS, SDS, cancer-related fatigue and quality of life between the two groups before intervention (P > 0.05). Conversely, after the intervention, the scores of FoP-Q-SF, SAS, SDS and cancer-related fatigue in the intervention group were significantly lower than those in the control group, and the scores of life quality in the intervention group were significantly higher than those in the control group (all P values < 0.05).Conclusion: Our findings provide evidence that comprehensive nursing based on cognitive behavior can effectively improve the negative psychological state of patients such as anxiety and depression and cancer-related fatigue with improved life quality for patients harboring glioma.Keywords: comprehensive nursing based on cognitive behavior, glioma, psychological function